PENGARUH UKURAN PEMERINTAH DAERAH, UKURAN LEGISLATIF, JUMLAH PENDUDUK, INTERGOVERNMENTAL REVENUE TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH PADA KABUPATEN/KOTA PROVINSI JAWA TIMUR - Nuriska Gusnaini, (2020)
This study aims to examine the effect of the level of disclosure of local government financial statements with the size of local government, legislative size, population, intergovernmental revenue. This research uses the Regency / City Regional Government in East Java Province 2016-2018. Sampling uses a census sampling method which is 114 samples in the District / City Government in East Java Province. Testing the hypothesis in this study is multiple linear regression with SPSS. The results of this study are that the size of the local government has no effect on the financial statements, the size of the legislature has no effect on the financial statements, the population has a significant effect on the financial statements, intergovernmental revenue has a significant effect on the financial statements. the contribution in this research to the local government is that it can provide suggestions for improving the quality of financial reports and local government governance. Keywords: Size of Local Government, Legislative Size, Population, Intergovernmental Revenue, Level of Financial Statement Disclosure.